The presence of anhedonia in individuals with subacute and chronic stroke: an exploratory cohort study - Segura, Emma; Vilà-Balló, Adrià; Mallorquí, Aida; Porto, María F.; Duarte, Esther; Grau-Sánchez, Jennifer; Rodríguez-Fornells, Antoni (Frontiers in Aging Neuroscience, 2024)
Background: Anhedonia refers to the diminished capacity to experience pleasure. It has been described both as a symptom of depression and an enduring behavioral trait that contributes its development. Specifically, in stroke patients, anhedonia has been closely linked to depression, resulting in reduced sensitivity to everyday pleasures and intrinsic motivation to engage in rehabilitation programs and maintain a healthy active lifestyle. This condition may hinder patients’ recovery, diminishing their autonomy, functioning, and quality of life. Objective: We aimed to explore the prevalence and level of anhedonia and those variables that might be associated in patients with both ischemic and hemorrhagic stroke at subacute and chronic phases of the disease. Method: We conducted an exploratory cohort study with a sample of 125 patients with subacute and chronic stroke presenting upper-limb motor deficits. We measured participants’ level of anhedonia with four items from the Beck Depression Inventory that describe the symptoms of this condition: loss of pleasure, loss of interest, loss of energy, and loss of interest in sex. We also collected demographic and clinical information and evaluated motor and cognitive functions as well as levels of depression, apathy, and various mood states. The results were compared to a sample of 71 healthy participants of similar age, sex, and level of education. Results: Stroke patients demonstrated a significantly higher prevalence (18.5-19.7%) and level of anhedonia compared to the healthy controls (4.3%), regardless of stroke phase, level of motor impairment, and other clinical variables. Furthermore, post-stroke anhedonia was associated with lower levels of motivation and higher levels of negative mood states such as fatigue and anger in the long term. Importantly, anhedonia level was superior in stroke patients than in healthy controls while controlling for confounding effects of related emotional conditions. Conclusion: This study provides novel evidence on the prevalence, level and factors related to anhedonia post-stroke. We emphasize the importance of assessing and treating anhedonia in this population, as well as conducting large-scale cohort and longitudinal studies to test its influence on long-term functional and emotional recovery.